A Distal to Proximal Gradient of Human Choroid Plexus Development, with Antagonistic Expression of Glut1 and AQP1 in Mature Cells vs. Calbindin and PCNA in Proliferative Cells - Castañeyra-Ruiz, Leandro; González-Marrero, Ibrahim; Hernández-Abad, Luis G.; Carmona-Calero, Emilia M.; Meyer, Gundela; Castañeyra-Perdomo, Agustín (Frontiers in Neuroanatomy, 2016)
The choroid plexuses (ChP) are highly vascularized tissues suspended from each of the cerebral ventricles. Their main function is to secret cerebrospinal fluid (CSF) that fills the ventricles and the subarachnoid spaces, forming a crucial system for the development and maintenance of the CNS. However, despite the essential role of the ChP–CSF system to regulate the CNS in a global manner, it still remains one of the most understudied areas in neurobiology. Here we define by immunohistochemistry the expression of different proteins involved in the maturation and functionality of the ChP from the late embryological period to maturity. We found an opposite gradient of expression between aquaporin 1 (AQP1) and glucose transporter 1 (Glut 1) that define functional maturation in the ChP periphery, and proliferating cell nuclear antigen (PCNA) and calbindin (CB), present in the ChP root zone with proliferative activity. We conclude that the maturation of the ChP matures from distal to proximal, starting in the areas nearest to the cortex, expressing in the distal, mature areas AQP1 and Glut1 (related to ChP functionality to support cortex development), and in the proximal immature areas (ChP root) CB and PCNA related to progenitor activity and proliferation.